Exploring Human Resources Development as a Determining Factor for Organizational Success: A Qualitative Approach - Pahala, Yosi; Haryanto, Anung; Nurhidayati, Ninin; Subehana, Subehana; Sidjabat, Sonya (Dinasti International Journal of Management Science, 2025)
This research explores the strategy of human resource development in Jakarta universities in the face of digital transformation and the Independent Learning Independent Campus (MBKM) policy, as well as the role of digitalization of HR management (Digital HR) in increasing organizational effectiveness. The method used is a qualitative approach with secondary data analysis from national and international journals over the past ten years. The results show that HR competence is the main factor in organizational success in the digital era. Technology-based HR development strategies, with stakeholder support, produce adaptive, innovative, and globally competitive human resources. Organizations that are responsive to technological and social change tend to have an edge over the competition. This study has limitations, such as the use of secondary studies that are not representative of all organizations, and has not been in-depth analyzing organizational cultural factors, technological readiness, and policy support. The absence of primary data also makes the research results theoretical. Nevertheless, these findings make an important conceptual contribution and can serve as a basis for further research in developing HR management models that are relevant to the demands of the digital age and the implementation of MBKM policies.